The Iberian challenge : creole languages beyond the plantation setting - Deutscher Hispanistentag 2013 : Münster, Germany); McWhorter, John H.; Schwegler, Armin, 1955-; Ströbel, Liane (Madrid : Iberoamerican : Vervuert, 2016)
"Creole languages lexified by Spanish and Portuguese have played a relatively small role in theories of creole genesis, and as a result the histories of vernaculars such as Palenquero, Papiamentu, Cape Verdean Creole, and the Gulf of Guinea creoles (e.g., São Tomense or Annobonese) have typically been considered distinct evolutionary events. In contrast, English and French-based creoles (e.g., Hawaiian Pidgin English or Haitian French), formerly spoken on large-scale plantations, have always been viewed as the "default" or prototypical kind. This volume takes issue with this traditional view by arguing that there is no a priori reason to give plantation creoles this preferential treatment. As the ten articles assembled here show, the plantation scenario is only one of many a realization that poses special challenges to theories of creole genesis that seek to be maximally comprehensive. Overall, Iberian-based creoles thus demonstrate a diversity of complex circumstances that any overarching theory of creole genesis ought to take into account."--P. [4] of cover.
Introduction / Armin Schwegler, John McWhorter & Liane Ströbel -- Once more on the genesis of West African Portuguese creoles / Alain Kihm & Jean-Louis Rougé -- The missing Spanish creoles are still missing: revisiting Afrogenesis and its implications for a coherent theory of creole genesis / John McWhorter -- On the relevance of Classical Portuguese features in four Atlantic creoles / Bart Jacobs & Nicolas Quint -- Documenting 17th-century Língua de Preto: evidence from the Coimbra archives / Ana R. Luís & Paulo Estudante -- Macau Pidgin Portuguese and Creole Portuguese: a continuum? / Michelle Li -- Philippine Creole Spanish ("Chabacano"): accusative marking in Caviteño. Grammatical and discursive functions / Marilola Pérez -- Palenquero and Spanish: what's in the mix? / John M. Lipski -- How psycholinguistics can inform contact linguistics: converging evidence against a decreolization view of Palenquero / Paola E. Dussias, Jason W. Gullifer & Timothy J. Peopsel -- Reconstructing the linguistic history of palenques. On the nature and relevance of colonial documents / Miguel Gutiérrez Maté -- Truth reset: pragmatics in Palenquero negation / Armin Schwegler.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2019. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Creole dialects -- Congresses; Creole dialects, Portuguese -- History -- Congresses; Creole dialects, Spanish -- History -- Congresses; Dialectos criollos -- Congresos; Dialectos criollos, portugués -- Historia -- Congresos; Dialectos criollos, español -- Historia -- Congresos; Libros electrónicos